Role of Clinical Laboratories in Reporting Laboratory Results of Transgender Individuals on Hormonal Therapy - Boitumelo Phiri-Ramongane (Journal of Medical Biomedical and Applied Sciences, 2021)
Transgender individuals experience discordance between their gender identity and sex assigned at birth as compared to their Cisgender counterparts. To relieve the disconnection between their identity and their bodies most take hormonal therapy which leads to notable changes in several laboratory results. With transgender population not having specific reference ranges like their counterparts their laboratory results may possibly misinterpreted which could lead to misdiagnosis or inappropriate management. The aim of the review is to explore the challenges experienced by clinicians in interpreting laboratory results for transgender individuals on hormonal therapy and to report on the available strategies used to interpret these results. Establishing reference intervals for the Transgender individuals will assist in correct interpretation of patient’s results and their management. This will also maximize their overall health, psychological well-being, and self-actualization.